Biodiversity and new occurrences of phytoplanktonic and periphytic Cyanobacteria from mangroves of northeastern Brazil - Vieira, Paulo Henrique Santos; Moura, Ariadne Do Nascimento; Gama, Watson Arantes (Phytotaxa, 2026)
Estuaries and their associated forests together comprise the mangrove ecosystem, one of the most productive environments on the planet and characterized by distinctive euryhaline biodiversity. Although Brazil possesses the world’s second largest expanse of mangroves, comprehensive knowledge regarding the organisms inhabiting these systems, including cyanobacteria, remains limited, a pattern also observed globally. This gap is particularly pronounced in Brazil’s northeastern region, where studies on cyanobacterial diversity in mangroves are scarce, especially those incorporating morphometric and taxonomic analyses. Herein, we aimed to identify and characterize phytoplanktonic and periphytic cyanobacteria from four mangrove systems along the northeastern Brazilian coast: the Barra de Jangadas Estuarine Complex, Santa Cruz Estuarine Complex, Formoso River Estuary, and Una River Estuary. Phytoplankton samples were collected using a 20 μm mesh plankton net at three distinct sites within each estuary, representing different sections along the salinity gradient (upstream, middle, and mouth). Sampling was conducted during both tidal periods. Periphyton samples were mostly obtained from Rhizophora mangle pneumatophores located near the phytoplankton sampling sites during low tide. A total of 66 cyanobacterial taxa were recorded, comprising 51 species, 10 generic-level taxa, three taxa identified as “cf.,” and two as “aff.,” distributed among 30 genera and 19 families. Oscillatoriaceae was the most representative family, with 27 infrageneric taxa identified. Notably, 15 of the taxa identified are new records for Brazil, and 22 are newly reported for the Brazilian Northeast. The significant diversity documented in this study, including numerous new occurrences, highlights the prominence of cyanobacterial biodiversity in these mangrove environments and highlights the substantial knowledge gap regarding their taxonomy in tropical estuaries and mangrove forests. The discovery of unclassified taxa further suggests the presence of species potentially new to science, emphasizing the importance of these ecosystems as reservoirs of novel cyanobacterial diversity.